Video Games: Their Influence on English as a Foreign Language Vocabulary Acquisition (GIST – Education and Learning Research Journal, 2019)
In this particular project, a four-week video game-based activity is proposed, using videogames as main sources to improve participants' vocabulary. Moreover, the data gathered in the project is triangulated by using tests, teacher's journal, and students' journal during the four weeks. The project aims to demonstrate the bond between videogames and vocabulary acquisition as well as breaking the superstition that videogames cannot be helpful in EFL contexts. Besides, during the activity, students are asked to play two games, Scribblenauts and Age of Empires II. Consequently, the research tries to understand and analyze the process and roles students and teachers develop through the usage of videogames in an EFL classroom; reflecting upon experiences from the games.
Keywords: video games; game-based learning; vocabulary acquisition; EFL